Economic crises and paradigm changes - Castañeda, Gonzalo (Estudios Económicos de El Colegio de México, 2010)
This essay suggests that the orthodox economic theory is in a quandary because of its poor performance in explaining the international financial crisis that started in 2008. Likewise, it claims that the social complexity theory is a better paradigm to explain socioeconomic phenomena, especially those characterized by endemic disequilibrium and non-linear collective behavior. In particular, the paper makes reference to models of heterogeneous agents based on statistical mechanics which explain the observed behavior in assets prices much better than the neoclassical models of efficient markets.